Aroclor 1254 impairs sperm quality, fertilization ability, and embryo development of rainbow trout (Oncorhynchus mykiss) - Kocabas, Mehmet; Kocabas, Filiz Kutluyer; Aksu, Onder; Benzer, Fulya; Erisir, Mine; Sahilli, Yeliz Cakir (Springer Heidelberg, 2022)
The polychlorinated biphenyls (PCBs) in aquatic environment adversely affect non-target organisms, including fish. Especially, the male reproduction and next generation can be damaged through high exposure to these pollutants. Hence, the sperm cells were exposed to sublethal concentrations of Aroclor 1254 (0, 1, 5, 10, or 25 mg/l) for 4 h. The sperm quality parameters were analyzed by SCA (Sperm Class Analyzer). The fertility, eyeing, and hatching rates were determined as gamete markers. Lipid peroxidation (malondialdehyde-MDA), glutathione (GSH), and antioxidant enzymes [superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT)] were measured for determination of oxidative stress. Our results showed that Aroclor 1254 negatively affected the motility rate and duration, fertilization rate, embryogenesis, and hatching and also triggered antioxidant defense mechanisms at the highest concentration (25 mg L-1). Furthermore, linear speed (VSL), linearity index (LIN), and amplitude lateral head (ALH) were significantly changed after exposure to 25 mg L-1, and the lowest concentrations (1 and 10 mg L-1) did not significantly affect the motility and fertilizing capacity. The embryogenesis and hatching were significantly affected by sperm exposure to 1, 10, and 25 mg L-1 of Aroclor 1254. Consequently, Aroclor 1254 causes potential hazards in male germ cells, and the exposure of sperm cells to pollutants can adversely affect next generation of wild populations.
Keywords: Aroclor 1254; Spermatozoa; Oncorhynchus mykiss; Oxidative stress; Embryo development